Membangun Kemampuan Literasi Anak Melalui Dongeng dan Permainan Tradisional - Nikmatul Azizah (Jurnal Kualita Pendidikan, 2021)
Literacy is a child's ability to read, understand and process information, literacy skills are needed by children to interact with other people. Literacy learning in schools is mostly done by reading, writing, and thickening writing. Teachers' knowledge of literacy is also still limited, so that the learning presented is monotonous and does not attract children's interest. so the kids get bored. The purpose of this study was to determine the development of children's literacy skills and the effectiveness of fairy tales and traditional games as a medium to develop children's literacy skills. This research was conducted in class B POS PAUD Anggun Poncol Pekalongan City with a total of twelve children. Data collection techniques using observation, interviews and tests. The data analysis used one group pre-post-test, the average level of children's literacy skills before the application of fairy tale strategies and traditional games was 53.5, after applying treatment with fairy tales and traditional games the average literacy ability of children increased to 89.92, p. This shows that the method of fairy tales and traditional games is effective as a medium to develop children's literacy skills.